Migration and separation among Latinx asylum seekers: Experiences and relations with anxiety and depression - Amanda Venta; Ashley Bautista; Maria Cuervo; Alfonso Mercado; Luz Garcini; Cecilia Colunga-Rodríguez; Mario Ángel-González (Journal of Affective Disorders Reports)
This study sought to describe the experiences of families seeking asylum at the U.S./Mexico border and explore how traveling with and without family was associated with mental health in a large group of Latinx adults. Additionally, we explored relations between experiences of family separation due to migration and anxiety and depression. N = 400 participants were recruited from two main locations: an encampment site along the Rio Grande River in Reynosa Tamaulipas, Mexico and a respite center serving families recently released by U.S. Customs and Border Protection in McAllen, Texas. The average age of participants was 31.35 years (SD = 9.30), and the gender distribution was as follows: 56.5 % identified as female, 41.8 % identified as male, and 1.8 % identified as transgender. All participants identified as Latinx and completed interview-based measures, including a demographic form, migration interview, and the Patient Health Questionnaire in Spanish. Results indicated that most participants (56 %) traveled with minor children and doing so was associated with increased anxiety and depressive symptoms, with neutralization of this effect when traveling with a spouse. All participants endorsed experiencing family separation due to migration and a relation between separation and symptoms of depression was noted, with particular vulnerability among a subset of participants who declined to discuss the separation. The findings of this study bring attention to a large and ongoing humanitarian crisis at the U.S.’s Southern border which renders Latinx asylum seeking families more vulnerable to affective disorders due to the traumatic and destabilizing effects of family separation.